The relationships among self-control, psychological resilience, and digital addiction in college students: a meta-analytic structural equation modeling - Zhao, Ziyang; Zhang, Yaozhong; Ma, Yongqiang; Obaid, Azeem; Zhu, Haidong (Frontiers in Psychology, 2025)
PurposeDigital addiction adversely affects the physical and mental well-being of college students. Comprehensive studies demonstrate that self-control has an inhibitory influence on digital addiction, with psychological resilience acting as a crucial mediating variable connecting self-control and digital addiction. Nevertheless, meta-analytic evidence supporting this mediating role is limited.Materials and methodsA meta-analysis employing structural equation modeling was conducted to examine the influence of self-control on digital addiction among college students. It encompassed 84 research studies and a total sample of 60,966 participants.ResultsThe findings indicate that psychological resilience modulates the connection between self-control and digital addiction, whereas self-control significantly influences digital addiction. This data suggests that when individuals exert considerable self-control to manage scholastic constraints or social responsibilities, their psychological resources drastically deplete, resulting in heightened digital media consumption. Moreover, self-regulated behaviors bolster psychological resilience by fostering a collection of good experiences, thereby diminishing escapist reliance on digital media.ConclusionThese findings elucidate the mediating process between self-control and digital addiction in college students, offering new intervention options and enhancing research on restricted self-control theory.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/DUZQM.